Poly (Ethylene Glycol) / Gelatin Composite Hydrogels for Drug Delivery - Ayhan, Fatma; Demirci, Sabiha; Ayhan, Hakan (Journal of Composites and Biodegradable Polymers, 2014)
Hydrogels are three dimentional, hydrophilic, and polymeric networks that have been designed and fabricated to fulfill the needs of the pharmaceutical and medical fields. Many biomedical applications including controlled drug delivery have developed based on hydrogel technologies. Various composite hydrogels including synthetic and natural materials can be produced to create controllable systems in drug delivery applications. In this study, poly(ethylene glycol) (PEG-DA) based composite hydrogels were prepared by photopolymerization method and 2,2-dimethoxy-2-phenylacetophenone (DMPA) was used as photoinitiator. Macromer mixtures were prepared by mixing 30 % PEG-DA and 0.5 % DMPA. Photocuring was achieved by cross-linking with 3 % ethylene glycol diacrylate (EGDMA) after addition of drug and gelatin solutions under mild conditions. The effect of gelatin concentration and molecular weight on the gentamicin release was studied with 75, 100, 225, and 300 bloom gelatin for 0.1, 0.5, and 1.0 w/w ratios. Drug release kinetics from loaded composite hydrogels were tested by spectrophotometric method in phosphate (pH 7.4) and citrate buffer (pH 1.2) representing small intestine and stomach media, respectively. New biopolymer containing composite hydrogels enhanced drug release rates for all compositions and gentamicin release was found to be adversely effected by concentration and molecular weight. Hydrogels were morphologically characterized by SEM images which indicated the presence of pinholes like structures with smaller sizes for larger molecular weights.